De-constructing disability: perspectives of persons with disability (PWD) in an African city - Prince Kwame Odame; Regina Obilie Amoako-Sakyi; Albert Abane; Dominic Edem Hotor (Cogent Social Sciences)
The dynamic context of people’s worldviews has resulted in different perspectives on the concept of disability. Inasmuch these narratives shed light on the multiplicity of definitions and connotations ascribed to disability, the literature on this subject has mostly been done in the Western world while ignoring the contextual setting of African countries like Ghana. This study explores the perspectives of persons with disability (PWDs) on the definition and connotation of disability in Ghana’s capital city of Accra by employing a qualitative research design. A sample of 50 PWDs were engaged through snowball and convenient sampling. The study’s findings reveal PWDs’ rejection of connotation that likens disability to sickness or a faulty population group. Despite this revelation, PWDs admitted that poor connotation of disability further reinforces doubt about their desire to prove themselves as valuable members of society.